1990
DOI: 10.1080/09553009014552611
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Radioprotector WR-2721 and WR-1065 on Mitochondrial Lipid Peroxidation

Abstract: The radioprotective agent WR-2721 is dephosphorylated to the free thiol form WR-1065 in vivo. The effects of WR-2721, WR-1065 and reduced glutathione on a mitochondrial lipid peroxidation system were compared. WR-2721 had no effect on mitochondrial lipid peroxidation in vitro, and could not prevent the inactivation of mitochondrial enzymes. Both WR-1065 and glutathione were effective inhibitors of mitochondrial lipid peroxidation induced by ADP/Fe/NADPH or by ADP/Fe/ascorbate. Both thiols correspondingly delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Immediate radioprotection of HMEC is the result of the localization of the free thiol WR1065 within two sensitive subcellular targets for radiation damage, the mitochondria and the nuclear DNA compartment [40,41]. If exposure to ionizing radiation occurs at this time, both of these sensitive targets can be protected.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate radioprotection of HMEC is the result of the localization of the free thiol WR1065 within two sensitive subcellular targets for radiation damage, the mitochondria and the nuclear DNA compartment [40,41]. If exposure to ionizing radiation occurs at this time, both of these sensitive targets can be protected.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, WR-1065 is not generally considered as a GSH inducer. Tretter et al [55] reported that WR-1065 and GSH were effective inhibitors of mitochondrial lipid peroxidation following a redox cycle implicating WR-1065, GSH, and GSH reductase. They suggested that these reactions might prevent the inactivation of mitochondrial enzymes necessary for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The GSSG is then reduced to GSH by GRd. 39 Protection of the mitochondria can be further facilitated through the development of antioxidants that are designed either for increased uptake into mitochondria, or to increase the activity of antioxidant enzymes. Linking the positively-charged functional group, alkyltriphenyl-phosphonium ion, to vitamin E or ubiquinone (CoQ) increased the uptake of these antioxidants into the mitochondrial matrix.…”
Section: Mitochondriamentioning
confidence: 99%